Phytochemical Screening Of Nardostachys Jatamansi (Jatamansi): Unveiling Its Therapeutic Bioactive Compounds - Kumari, Nagma; Sahiba, Sahiba; Naaz, Farha; Heena, Heena; Bhardwaj, Shivani; Kumar, Roshan; Gusain, Deeksha (Journal of Neonatal Surgery, 2025)
Nardostachys jatamansi (commonly known as Jatamansi) is a medicinal plant native to the Himalayan region, widely used in traditional medicine for its therapeutic properties. Phytochemical screening of Jatamansi is essential for identifying its bioactive compounds, which contribute to its pharmacological effects, including anti-inflammatory, antioxidant, and neuroprotective activities. This research presents an overview of the phytochemical constituents found in Nardostachys jatamansi and their potential medicinal applications. The preliminary phytochemical analysis of Nardostachys jatamansi root and aerial parts reveals the presence of a wide range of bioactive compounds, including alkaloids, flavonoids, tannins, saponins, phenolic compounds, glycosides, and essential oils. Alkaloids such as nardostachysin and jatamansone, found in the roots, are known for their sedative and anticonvulsant effects. Flavonoids, particularly quercetin, contribute to the plant's antioxidant properties, protecting cells from oxidative stress. Tannins and phenolic compounds exhibit strong antimicrobial and anti-inflammatory activities. Saponins and glycosides are noted for their immunomodulatory and anti-cancer properties, suggesting potential therapeutic applications in immune system regulation and cancer treatment. In conclusion, the phytochemical constituents of Nardostachys jatamansi play a vital role in its therapeutic efficacy, supporting its use in traditional medicine. However, further research, including clinical trials and advanced pharmacological studies, is necessary to validate its medicinal potential and optimize its therapeutic applications.